Adenoma size and postoperative IGF-1 levels predict surgical outcomes in acromegaly patients: results of the Swiss Pituitary Registry (SwissPit) (Swiss Medical Weekly, 2018)
AIMS OF THE STUDY Acromegaly due to a growth hormone-secreting pituitary adenoma is a rare disease with high morbidity if not treated adequately. Using data of the Swiss Pituitary Registry (SwissPit), we studied initial presentation and predictors for adverse clinical outcomes in acromegalic patients treated during the last 10 years in our institution. METHODS We evaluated 21 patients from the SwissPit registry with a final diagnosis of acromegaly confirmed by laboratory results (insulin-like growth factor-1 [IGF-1] and growth hormone suppression tests) and magnetic resonance imaging. Our main endpoint was clinical cure defined as complete remission, remission with need for medical treatment and uncontrolled disease defined by non-normalisation of IGF-1 and growth hormone levels. RESULTS The most prevalent clinical symptoms at presentation were acral enlargement (81%), headache (29%), macroglossia (29%) and visual field defects (19%). Arterial hypertension was present in 67%, carpal tunnel syndrome in 38% and diabetes in 24%. A total of 19 of the 21 patients underwent initial surgical treatment. Eight patients had complete remission and 13 patients had active disease, with 7 having remission with need for medical treatment and 6 uncontrolled disease. Larger initial adenoma size (odds ratio [OR] 12.0, 95% confidence interval [CI] 1.02–141.3; p = 0.048) and high post-operative IGF-1 levels (OR 4.5, 95% CI 1.1–19.2; p = 0.040) were predictors for non-full remission and uncontrolled disease, respectively. CONCLUSION This small, observational registry study showed a relevant success rate of initial pituitary surgery in patients with confirmed acromegaly. Initial tumour size and postoperative IGF-1 levels help to risk stratify patients regarding expected outcomes. In the case of disease persistence, a multimodal approach using drug and radiotherapy is mandatory.